Who Believes in Homo Deus?: A Posthuman Belief Questionnaire that Explores Public Views on the Future of Humanity - Spiekermann, Sarah (Philosophy, theology and the sciences, 2024)
This article presents the complex landscape of philosophical and anthropological thought on our human future, partially referred to as "posthumanism". Building on a categorization of posthuman narratives presented by Tamar Sharon (2014) that dis- cerns liberal, dystopic and radical posthuman narratives, a survey instrument was built and statistically tested on 300 Germans and Austrians. The posthuman identity survey developed in this article explores and structures public beliefs in the future of humanity and its underlying philosophical and anthropological dimensions. It statistically identifies that posthuman narratives can be best captured by differen- tiating between critical conservative, transhuman, tech-liberal and radical political perspectives on our human future. Applying the survey instrument to the popula- tion studied, it turns out that two-thirds of the representative educated German/ Austrian sample share in a critical conservative ideal of humanity ('Menschenbild'). Meanwhile,'Homo Deus' or transhuman narratives, which often embrace a computer anthropology, are only shared by twenty percent of the population, mostly young males with introvert self-comparison traits.